Borehole seismic survey using multimode optical fibers in a hybrid wireline. (September 2018) - Yu, Gang; Cai, Zhidong; Chen, Yuanzhong; Wang, Ximing; Zhang, Qinghong; Li, Yanpeng; Wang, Yanhua; Liu, Congwei; Zhao, Baoyin; Greer, Joe
Highlights: DAS uses optical fiber cable as distributed sensors for borehole seismic signals. DAS is a viable alternative to downhole geophone arrays for borehole seismic survey. It can dramatically reduce operating time required for a borehole seismic survey. It can achieve much higher spatial coverage than is typical of current technologies. Optical cable for borehole seismic survey will open DAS to much wider applications. Abstract: Distributed Fiber Optic Sensing is increasingly recognized as a viable alternative to geophone arrays for the acquisition of borehole seismic data. The ability to deploy optical fibers into a well, either as a cable based intervention or as part of a completion string, allows for the entire wellbore to be surveyed with every source activation. This can dramatically reduce the operating time required to complete a normal survey as well as offering the opportunity to achieve much higher spatial coverage than is typical of current technologies. The ability to acquire borehole seismic data in a producing well without the need to disrupt production also offers significant benefits to the operator. Distributed acoustic sensing (DAS) is a novel technology that uses an optical fiber cable as a sensor for acoustic signals and can take almost any downhole fiber-optic installation or deployment and turn the fiber optic cable into a large downhole seismic array. This array can provide enhanced Vertical Seismic Profile (VSP) imaging and monitor fluids and pressures changes in the hydrocarbon production reservoir. Walkaway VSP data acquired over a former producing well in north eastern China provided a rich set of very high quality DAS Walkaway VSP data. A standard VSP data pre-processing workflow was applied, followed by prestack Kirchhoff time migration. In the DAS pre-processing step we were faced with additional and special challenges: strong coherent noise due to cable slapping and ringing along the borehole casing. In comparison with an earlier offset VSP data set using 327-levels acquired with conventional 3C downhole geophones in the same well, the final pre-processed DAS walkaway VSP has a larger vertical aperture resulting in a wider lateral image. The single well DAS Walkaway VSP images provide a good result with higher vertical and lateral resolution than the surface seismic in the objective area. The vertical well environment without the ability to effectively "clamp" the sensor to the borehole casing wall by touching, creates a unique set of challenges. Although earth signal was recorded with almost all the shots, there was also a considerable amount of noise. Much of the noise was due to the physical placement of the wireline in the well and expressed by slapping and ringing. This paper reports on lessons learned in the handling of the wireline cable and subsequent special DAS data processing steps developed to remediate some of the practical wireline deployment issues. Optical wireline cable as a conveyance of fiber optic cables for VSP in vertical wells will open the use of the DAS system to much wider applications.